Perilaku dalam Implementasi Kebijakan Penegakan Hukum Lalu Lintas Elektronik di Direktorat Lalu Lintas Polda Jawa Barat - R Widya Setiabudi Sumadinata; Ramadhan Pancasilawan; Rivai, Sigit Ariansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
E-TLE (Electronic Traffic Law Enforcement) is a technology implementation from the Indonesian National Police that synergizes with other stakeholders to record traffic violations electronically to support traffic security, order, and safety. In the E-TLE policy, of course, some activities provide color to the implementation of the E-TLE policy itself. The research method used in this study is a qualitative approach with a descriptive method. Data collection is done through literature studies, documentation studies, and results of relevant reports. The results of the study show that there is behavior between related organizations, the behavior of lower-level bureaucracy as policy implementers, and related to the behavior of the target group of the policy, all of which are interrelated and have their respective influences on the E-TLE (Electronic Traffic Law Enforcement) policy